Pengaruh Media Sosial atau Lingkungan Pergaulan?: Mengungkap Determinan Utama Motivasi Berhijrah - Widyaningsih, Rindha (Assertive: Islamic Counseling Journal, 2022)
The phenomenon of hijrah encountered its momentum because the leading enthusiasts for hijrah came from among young people. This study aims to examine the main determinants of motivation to hijrah. The two arguments tested in this study are the influence of social media and the influence of the social environment. The data collection method used in this study was a closed questionnaire consisting of questions related to the motivation to hijrah. A literature review supports the study results to strengthen the analysis results. The research respondents were Banyumas residents who were selected through purposive sampling. The questionnaire consists of 4 answer options, specifically Strongly Agree (SS) is given a score of 4, Agree (S) is given a score of 3, Disagree (TS) is given a score of 2, and Strongly Disagree is given a score of 1. The primary determinant of hijrah is determined through the index results by calculating a predetermined formula. The results showed that the social media influence factor index was higher than the social environment influence factor index. The social media influence index is 19.03, while the social environment influence factor is 12.43. Based on the index number, it can be concluded that the influence of social media is the primary determinant of a person's motivation to hijrah. The study's results stated that the primary determinant of motivation to hijrah was the influence of social media (Hypothesis accepted).